2019
DOI: 10.1186/s41687-019-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a framework with tools to support the selection and implementation of patient-reported outcome measures

Abstract: Background: Patient reported outcomes (PROs) provide information on a patient's health status coming directly from the patient. Measuring PROs with patient reported outcome measures (PROMs) has gained wide interest in clinical practice for individual patient care, as well as in quality improvement, and for providing transparency of outcomes to stakeholders through public reporting. However, current knowledge of selecting and implementing PROMs for these purposes is scattered, and not readily available for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 22 publications
0
68
0
Order By: Relevance
“…PRO is an important component of public health surveillance and its assessment outcomes are increasingly being used as an indicator to address broader areas of public policy [15,16,37]. This is particularly important in conditions such as LTBI, where it can be used to obtain medical management feedback from affected individuals including issues related to treatment side effects, depression, distress or anxiety which may affect their quality of life and treatment completion rate [15,16]. This indirectly determines the burden of preventing TB re-activation and to guide the development of new strategic plans for future community-based interventions with quality integrated care among individuals with LTBI, helping towards achieving the WHO End TB Goal by 2035.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRO is an important component of public health surveillance and its assessment outcomes are increasingly being used as an indicator to address broader areas of public policy [15,16,37]. This is particularly important in conditions such as LTBI, where it can be used to obtain medical management feedback from affected individuals including issues related to treatment side effects, depression, distress or anxiety which may affect their quality of life and treatment completion rate [15,16]. This indirectly determines the burden of preventing TB re-activation and to guide the development of new strategic plans for future community-based interventions with quality integrated care among individuals with LTBI, helping towards achieving the WHO End TB Goal by 2035.…”
Section: Discussionmentioning
confidence: 99%
“…In patient-centred care practice, PRO measures play an important role in capturing patients' subjective perceptions of health evidence of treatment response, physical symptoms, psychological challenges, quality of life and wellbeing. This helps in addressing patients' unmet needs to improve the quality of care with a valued outcome in a holistic health service [15,16]. This review aims: 1) to identify studies that reported the health and wellbeing of individuals diagnosed with LTBI; 2) to evaluate the impact of LTBI on HRQoL compared with patients with active TB disease and individual without TB infection; and 3) to assess the psychometric properties of health outcome instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported measures play an important role in patientcentred healthcare and can improve communication, patient engagement, and self-efficacy as patients may be more involved in goal setting [33][34][35]. The use of a patientreported measure, however, may be limited by patients who experience cognitive and/or language comprehension deficits.…”
Section: Patient-reported Measuresmentioning
confidence: 99%
“…The use of a patient-reported measure, however, may be limited by patients who experience cognitive and/or language comprehension deficits. Recently, a framework (patient-reported outcome measures or PROM-cycle) was developed to support the selection and implementation of patient-reported measures in individual patient care and for quality improvement [ 35 ]. The PROM-cycle describes eight steps necessary for systematic selection and implementation of PROMs in a cyclic approach and provides links to, for example, relevant tools and existing guidelines, examples from clinical practice and methodological considerations.…”
Section: Non-instrumental Assessmentmentioning
confidence: 99%
“…Important concepts identified from patient insights can inform the selection of suitable patient-reported outcome (PRO) instruments for use in clinical trials, observational studies, and clinical practice. Indeed, guidelines have been developed for both the development of PRO measures for clinical studies, and the selection and implementation of them in practice [ 12 , 14 ]. While the Australian Canadian Osteoarthritis Hand Index (AUSCAN) is widely used and has been developed for use in HOA [ 15 , 16 ], as indicated in a study of its use in patients with rheumatoid arthritis, it is a measure of pain, stiffness and function, and does not measure the emotional and behavioral consequences of pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%